Shadow Children: Among the Hidden - Book 1 - Haddix, Margaret Peterson (New York : Simon & Schuster Books for Young Readers, 1998)
In a future where the Population Police enforce the law limiting a family to only two children, Luke has lived all his twelve years in isolation and fear on his family's farm, until another "third" convinces him that the government is wrong.
Keywords: Population -- Juvenile fiction; Totalitarianism -- Juvenile fiction; Population -- Fiction; Totalitarianism -- Fiction; Science fiction; Junior Fiction